Natural Disasters Management in Indonesia: Perspective of Local Wisdom and Heidegger Hermeneutics - Idaman Alwi; Rizal Mustansyir; Protasius Hardono Hadi (Al-Albab, 2017)
Natural disaster managements in Indonesia carried out by the government seemed centralized, slow and is not well prepared. Even the government seems to ignore the management of natural disasters that has long been entrenched in the pulse of local community knowledge systems. Considerations in decision-making mitigation of natural disasters is too scientific-positivistic and ignores the philosophical aspect of the work. This paper attempts to offer a perspective of natural disaster management with support of Indonesian local wisdom and Heidegger hermeneutics. Most of the ethnic groups in Indonesia have already had a set or system of knowledge in the management of natural disasters. This knowledge system exists since the long experience of Indonesian society in dealing with natural disasters. This system is then passed on and transformed from many generations through oral hystory. Some studies indicate that local knowledge systems on the management of natural disasters so far   are very effective in minimizing the number of dissaster victims. In addition, Martin Heidegger hermeneutics offeres a concept of natural disaster management with the starting point of the idea of being-in-the-world.The idea is one of the basic principles of hermeneutics-facticity Martin Heidegger who supposes that a real human living being has awareness of this universe. In the 'living earth', man does not necessarily accept the fate thrown into the earth, but he has the ability to exercise the creativity for survival. As a result of the awareness of the throwness into the universe, in turn, human beings have awareness that they have a relation to one another, empathy and sensitivity as human beings.